Incidencia y distribución geográfica de la enfermedad de Parkinson en México - Daniel Martínez-Ramírez; Mayela Rodríguez-Violante; Edna Sophia Velázquez-Ávila; Amin Cervantes-Arriaga; Arnulfo González-Cantú; Teresita Corona-Vázquez; Leora Velásquez-Pérez (Instituto Nacional de Salud Pública, 2020)
No disponible